Field Study of Ohio's Structural Support Inspection Program for Overhead Signs, Traffic Signals, and High-Mast Lights. Issue 1 (2016) - Ghaedi, Hamed; Nims, Douglas; Gostautas, Richard; Steinberg, Eric; Hu, Liangbo; Walsh, Kenneth
The Ohio Department of Transportation (DOT) undertook a field study to evaluate its overall structural inspection programs for overhead sign supports (including those mounted on bridges), high-mast light supports, and traffic signal supports. This paper describes the Ohio DOT's current support inspection program, the field study performed, and the recommendations that resulted from the field study. This research evaluated the adequacy and frequency of the current structural support inspection program for the studied supports. To assess the current program, a detailed, hands-on inspection was conducted on 202 supports. The results were then compared with the Ohio DOT's current ground-based, visual inspection process. The hands-on inspection process found almost 87% more deficiencies; some deficiencies detected during the hands-on inspections could not have been observed from the ground. In addition, the different inspection procedures used by each district often produced inspection reports that varied in the amount of information and level of details collected during inspection. Recommendations were made to address the inventory process and inspection procedures for each type of support. A long-term goal should be to establish the current structural adequacy of every support in the Ohio DOT's inventory at the time of inspection.